Hermetic bags remain effective in minimizing storage loss after four successive cycles of reuse in Mexican highlands - Odjo, Sylvanus; González Regalado, Jessica; Saldivia Tejeda, Abel; Guera, O.G. Mariel; Verhulst, Nele (Elsevier, 2025)
Maize and beans are two important crops in Mexico that are heavily infested by insect pests during storage, which can cause significant damage and jeopardize the food security of smallholder farmers. The effectiveness of polypropylene bags in minimizing storage loss was compared to the effectiveness of four hermetic bags from three different manufacturers (GrainPro Inc., USA; Ecotact, India; Vestergaard Frandsen Inc., Switzerland) and the effectiveness of silage plastic bags. The assessment was performed on maize and bean grain during four different cycles of storage for three months using the same hermetic bags. The bags were repaired with tape when perforated by insects to assess the effect on storage loss of reusing hermetic bags during consecutive storage cycles. Data were collected on the number of holes per bag, moisture content, insect damage, and weight loss before and after each storage cycle. All bags were perforated after the first cycle of storage; the silage plastic bag was the most affected and had to be changed after the second storage cycle. These perforations were caused by the activity of insects inside the bags in their attempt to escape the low-oxygen conditions created by the bags’ airtightness. Polypropylene bags showed severe insect damage, reaching 15.6% during the second storage cycle. Hermetic bags, on the other hand, consistently maintained a moisture content below 13%, insect damage below 5%, and weight loss below 2%, even after being perforated by insects and repaired. All the hermetic bags tested are recommended for use by smallholders to minimize storage loss. Repairing and reusing hermetic bags is a good strategy that can help minimize storage loss while reducing costs and the impact of the use of plastic materials on the environment.